ICSE Class 10CISCE
Share
Notifications

View all notifications
Books Shortlist
Your shortlist is empty

If (3x – 4y): (2x – 3y) = (5x – 6y): (4x – 5y), Find X: Y. - ICSE Class 10 - Mathematics

Login
Create free account


      Forgot password?

Question

If (3x – 4y): (2x – 3y) = (5x – 6y): (4x – 5y), find x: y.

Solution

(3x - 4y) : (2x - 3y) = (5x - 6y) : (4x - 5y)

`(3x - 4y)/(2x - 3y) = (5x - 6y)/(4x - 5y)`

Applying componendo and dividendo

`(3x -4y + 2x - 3y)/(3x - 4y - 2x + 3y) = (5x - 6y + 4x - 5y)/(5x -6y - 4x + 5y)`

`(5x - 7y)/(x - y0) = (9x - 11y)/(x - y)`

`5x - 7y = 9x - 11y`

11y - 7y = 9x - 5x

4y = 4x

`x/y = 1/1`

x : y = 1 : 1

  Is there an error in this question or solution?

APPEARS IN

 Selina Solution for Selina ICSE Concise Mathematics for Class 10 (2018-2019) (2017 to Current)
Chapter 7: Ratio and Proportion (Including Properties and Uses)
Ex.7D | Q: 3

Video TutorialsVIEW ALL [1]

Solution If (3x – 4y): (2x – 3y) = (5x – 6y): (4x – 5y), Find X: Y. Concept: Ratios.
S
View in app×